Effectiveness of neem materials and biochar as nitrification inhibitors in reducing nitrate leaching in a compost-amended Ferric Luvisol - Abeka, Hammond; Lawson, Innocent Yao Dotse; Nartey, Eric; Adjadeh, Thomas; Asuming-Brempong, Stella; Bindraban, Prem; Atakora, Williams Kwame (Frontiers in Soil Science, 2022)
Nitrates produced after mineralization from compost may be prone to leaching, especially in tropical sandy soils, because of the increased rate of nitrification and the porous nature of such soils. This may result in low nitrogen (N) use efficiency and adverse environmental effects. Inorganic nitrification inhibitors are costly and mostly unavailable in Ghana. Research on simple but effective local materials for use as nitrification inhibitors is therefore a priority. Two such materials are neem materials and biochar. Neem materials can suppress nitrifying bacteria due to its antimicrobial properties. Biochar can hold ammonium in the soil, making it temporarily unavailable to nitrifying bacteria. This study seeks to determine the efficacy of neem materials and biochar as nitrification inhibitors and their influence on nitrate leaching. In preliminary studies: (1) pot incubation was conducted for 60 days to estimate the nitrification rate with manure, compost, and NH4Cl as the N source (150 kg N/ha) in one set and neem seeds, bark, and leaves (1.25 µg azadirachtin/g) in another set, using nitrate concentrations; and (2) ammonium sorption and desorption capacity of sawdust, rice husk, and groundnut husk biochar were determined. In the main study, pot incubation with compost as the N source but treated with milled neem seeds or bark (1.25 µg azadirachtin/g) or sawdust biochar (20 ton/ha) was conducted for 60 days, in which nitrification inhibition was determined using nitrate concentrations. A leaching experiment in columns with similar treatments and maize sown was then conducted to quantify the nitrate in leachates. A high nitrification rate was recorded in compost-amended soil, almost half that of the standard (NH4Cl). Sawdust biochar, which had the highest ammonium sorption and desorption capacity, resulted in 40% nitrification inhibition that lasted the entire incubation period). Neem seeds with an azadirachtin concentration of 3.92 mg/g resulted in similar nitrification inhibition, but this only lasted 40 days. Inhibition caused by both materials resulted in about a 60% reduction in nitrate leached. Thus, neem seeds (498 kg/ha) and sawdust biochar (20 mt/ha) could be used to control nitrate leaching for short-duration crops and long-duration crops, respectively.